Sebuah Analisis Terhadap Problematika Ajaran Restorasi Berkaitan Dengan Konsep Bumi Baru - Yudi Jatmiko (Sekolah Tinggi Teologi Intheos Surakarta, 2018)
Abstraks. The second coming of Christ is an event inalienable to mankind. In addition to declaring punishment for unbelievers, His second coming also fulfils the presence of a new heaven and earth in which the righteous will reign with Christ forever. Of this, the Bible records that